IK1 Channel Agonist Zacopride Alleviates Cardiac Hypertrophy and Failure via Alterations in Calcium Dyshomeostasis and Electrical Remodeling in Rats - Liu, Qing-Hua; Qiao, Xi; Zhang, Li-Jun; Wang, Jin; Zhang, Li; Zhai, Xu-Wen; Ren, Xiao-Ze; Li, Yu; Cao, Xiao-Na; Feng, Qi-Long; Cao, Ji-Min; Wu, Bo-Wei (Frontiers in Pharmacology, 2019)
Intracellular Ca2+ overload, prolongation of the action potential duration (APD) and downregulation of inward rectifier potassium (IK1) channel are hallmarks of electrical remodeling in cardiac hypertrophy and heart failure (HF). We hypothesized that enhancement of IK1 currents is a compensation for IK1 deficit and a novel modulation for cardiac Ca2+ homeostasis and pathological remodeling. In adult Sprague-Dawley (SD) rats in vivo, cardiac hypertrophy was induced by isoproterenol (Iso) injection (i.p., 3 mg/kg/d) for 3, 10 and 30 days. Neonatal rat ventricular myocytes (NRVMs) were isolated from 1-3-days SD rat pups, and treated with 1 μmol/L Iso for 24 h in vitro. The effects of zacopride, a selective IK1 /Kir2.1 channel agonist, on cardiac remodeling/ hypertrophy were observed in the settings of 15 μg/kg in vivo and 1 μmol/L in vitro. After exposing to Iso for 3 days and 10 days, rat hearts showed distinct concentric hypertrophy, fibrosis and enhanced pumping function (P < 0.01 or P < 0.05), then progressed to dilatation and dysfunction post 30 days. Compared with the age- matched control, cardiomyocytes exhibited higher cytosolic Ca2+ (P < 0.01 or P < 0.05) and lower SR Ca2+ content (P < 0.01 or P < 0.05) all through 3, 10 and 30 days of Iso infusion. The expressions of Kir2.1 and SERCA2 were downregulated, while p-CaMKII, p-RyR2 and cleaved caspase-3 were upregulated. Iso induced electrophysiological abnormalities were also manifested with resting potential (RP) depolarization (P < 0.01), APD prolongation (P < 0.01) in adult cardiomyocytes, and calcium overload in cultured NRVMs (P < 0.01). Zacopride treatment effectively retarded myocardial hypertrophy and fibrosis, preserved the expression of Kir2.1 and some key players in Ca2+ homeostasis, normalized the RP (P < 0.05), abbreviated APD (P < 0.01), thus lowered cytosolic [Ca2 +]i (P < 0.01 or P < 0.05). IK1channel blocker BaCl2 or chloroquine largely reversed the cardioprotection of zacopride. We conclude that cardiac electrical remodeling is concurrent with structural remodeling. By enhancing cardiac IK1, zacopride prevents Iso-induced electrical remodeling around intracellular Ca2+ overload, thereby attenuates cardiac structural disorder and dysfunction. Early electrical interventions may provide protection on cardiac remodeling.